Bullying Literacy Assistance in Improving Student Mentality - Muhammad Rizka Aditriyana; Zikri Fachrul Nurhadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The background to this service is the rise in cases of bullying in the school environment due to a lack of social interaction and, a lack of bonding with family and the school environment. Especially in the world of education, cases of physical bullying are 55%, verbal bullying is 30%, and cyberbullying is 15%. Students at SMK Negeri 2 Garut are 70% male-dominant, of course, acts of bullying will occur because the perpetrators and victims of bullying usually occur among men. The aim of holding this community service is to provide understanding and skills to individuals, especially children, and teenagers, so that they can recognize, prevent, and overcome bullying, so that children's mentalities can be honed and continue to improve. The method used in this service is mentoring through the Focus Group Discussion (FGD) method, which is a research data collection technique that ultimately produces information from interactions between several participants in a study, similar to other data collection methods in general. The result of this service is that students who initially only knew the basic definition of bullying, after being given this assistance almost all students understand what the bad effects of bullying are, the positive side of bullying has also been understood, such as becoming more sensitive. about the surrounding environment, sharpening a person's mentality for the future, as evidenced by the questionnaire results above 8.5%. We hope that after this service activity is held, there will be no more or fewer cases of bullying, either in the surrounding environment or cyberbullying on social media